Analysis of the Effect of Dust on the Efficiency of Solar Panels to Convert Electricity at the Al-Jadriya Site in the City of Baghdad (Iraqi National Journal of Earth Science (INJES), 2026)
This paper focuses on applied geography, specifically the spectral analysis of atmospheric dust and its impact on the photovoltaic efficiency of solar panels at the Baghdad—Al-Jadriya site. It aims to support the use of solar energy as a clean electricity source amid climate change and increasing dust activity. The research examines how atmospheric dust impacts solar radiation that reaches the Earth's surface, its accumulation on panels, and the resulting effects on electricity generation.  Climatic data from 1993-2023 were analyzed using statistical and analytical methods. Results show that Iraq’s climate is strongly influenced by continentality due to its distance from water bodies and the dominance of the subtropical high-pressure system in spring and the Indian thermal low in summer. These factors cause high temperatures, low humidity, and frequent dust activity. Spectral analysis confirmed suspended dust as the most prevalent and recurrent form over Baghdad. Field experiments conducted in 2022 and 2024 revealed two main dust effects. The positive effect was a reduction in panel temperature during clear days caused by dust deposition; for example, in June, solar radiation was 807 W/m², panel temperature 42.5°C, and peak power 175.7 W. The negative effect appeared during dust storms, causing atmospheric scattering and surface deposition that reduced radiation intensity and absorption; in October, radiation dropped to 678.9 W/m², panel temperature rose to 53.7°C, and power decreased to 135.15 W. These findings highlight the need to develop solar technologies adapted to arid and semi-arid climates.
Keywords: Continental impact, Dust, Electrical Conversion, Efficiency, Solar Panels, Dust Storms.